Kajian Aspek-Aspek Perancangan Creative Hub di Kabupaten Asahan - Nur Arba’atun Tsaniyah; Wahyuni Zahrah (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
The Creative Industry in Indonesia has experienced significant growth. However, it faces challenges such as low quality of human resources and inadequate facility accessibilityThe Creative Industry in Indonesia has experienced significant growth. However, the challenges lie in the low quality of human resources and inadequate accessibility to facilities. One solution is to provide creative hub facilities as centers for collaboration, innovation, and the development of the creative industry business. This research aims to analyze the aspects of creative hub in enhancing creativity and the development of the creative industry business in Kabupaten Asahan. The method used in this research is a mixed-method approach, combining qualitative and quantitative methods, involving a comparative study of buildings with similar functions and a survey using questionnaires with 30 respondents, particularly those who have used creative hubs and the general population of Kabupaten Asahan. The results show that creative hub facilities in Kabupaten Asahan play a crucial role in enhancing creativity and the development of the creative industry business. Users tend to prefer facilities that support collaboration and innovation, as well as those that provide comfort such as prayer rooms and green open spaces. This emphasizes the potential of creative hubs as centers for developing creative potential and the creative industry business in the Kabupaten Asahan area.